2018
DOI: 10.1136/bmjopen-2018-021898
|View full text |Cite
|
Sign up to set email alerts
|

Severe outcomes associated with respiratory viruses in newborns and infants: a prospective viral surveillance study in Jordan

Abstract: ObjectiveTo assess virus-specific hospitalisation rates, risk factors for illness severity and seasonal trends in children hospitalised with acute respiratory infections (ARI).DesignProspective cohort study.SettingA government hospital serving low-income and middle-income population in Amman, Jordan.ParticipantsChildren under 2 years of age hospitalised with fever and/or respiratory symptoms (n=3168) from 16 March 2010 to 31 March 2013. Children with chemotherapy-associated neutropenia and newborns who had nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 42 publications
3
60
1
Order By: Relevance
“…25 Apnea, though it lacked sensitivity, was a significant clinical predictor for severe RSV infection requiring hospitalization in infants <6 months. 22,[26][27][28] The reason for sepsis to be significantly less common amongst RSV-positive hospitalized young infants in this study in contrast to other studies 29,30 is unclear.…”
Section: Discussioncontrasting
confidence: 75%
“…25 Apnea, though it lacked sensitivity, was a significant clinical predictor for severe RSV infection requiring hospitalization in infants <6 months. 22,[26][27][28] The reason for sepsis to be significantly less common amongst RSV-positive hospitalized young infants in this study in contrast to other studies 29,30 is unclear.…”
Section: Discussioncontrasting
confidence: 75%
“…19 Although viral infection is the dominant cause of ARIs, the proportion of infections with atypical pathogens is increasing due to the abuse of antibiotics and the development of detection technology. [9][10][11] At present, several studies on the epidemiology and etiology of respiratory pathogens of children in different areas have been reported, 7,16,[20][21][22][23] The result of this study shows that the top three most prevalent pathogens were MP (18.12%, 2816/5597),Flu B (11.65%, 1811/5597) and CP (7.00%, 1088/5597). The total positive detection rate is 36.01% (5597/15443) in Xi'an, which was similar with the previous study in Turkey (33.4 ) and Shandong province in China (35.75 ), 12,18 and signi cantly higher than that reported in Beijing (5.64%), Shenzhen (14.55%), Suzhou (13.6%) and Gansu province in China (29.2%), [13][14][15][16] but lower than that reported in north China (39.3%).…”
Section: Discussionmentioning
confidence: 67%
“…Nascimento and colleagues reported a lower incidence (approximately 15% for RSV-A and 12% for RSV-B) of RSV cases in patients with community-acquired pneumoniae (CAP), which was not as severe as hospitalization [ 57 ]. Additionally, the Khuri-Bulos group detected >95% viral infections during the winter period in their studied population, with a predominance of RSV, mainly in younger patients (approximately 20% in subjects younger than 6 months) and in those with pneumonia (approximately 35%) [ 58 ].…”
Section: Incidence Of Respiratory Syncytial Virus (Rsv)mentioning
confidence: 99%
“…In general, signs and symptoms appear after a short incubation period, as for the majority of viruses, of approximately 4 days [ 78 ]. The already cited prospective viral surveillance study of Khuri-Bulos and colleagues reported a significantly lower presence of fever but a high probability of cough, shortness of breath, and flaring in patients with RSV infection [ 58 ]. It has been observed that RSV-A causes more severe illness than RSV-B; in fact, the two serotypes elicit a different response in terms of cytokine and neutrophil production [ 74 , 79 ].…”
Section: Clinical Manifestation Of Respiratory Syncytial Virus (Rsmentioning
confidence: 99%